Hillary Clinton - Fitzgerald, Stephanie (New York : Children's Press, 2017)
An illustrated biography of Hillary Rodham Clinton.
Includes index.
3.9
K-3
610L
Keywords: Clinton, Hillary Rodham -- Juvenile literature; Presidential candidates -- United States -- Biography -- Juvenile literature; Presidents' spouses -- United States -- Biography -- Juvenile literature; Legislators -- United States -- Biography; United States. -- Congress. -- Senate -- Biography -- Juvenile literature; Clinton, Hillary Rodham; Women -- Biography; Presidential candidates; Presidents' spouses; United States. -- Department of State; Legislators -- Biography; United States. -- Congress. -- Senate; Biographies